Xanthogranulomatous endometritis: A case report and literature review - Merviel, Philippe; James, Pandora; Carlier, Marianne; Thomas‐Kergastel, Isabelle; Guilloique, Marine; Conan‐Charlet, Virginie; Bastard, Clara; Marcorelles, Pascale; Jobic, Yannick; Dupré, Pierre‐François (Clinical case reports, 2021)
Xanthogranulomatous endometritis is a rare benign pathology mimicking endometrial carcinoma. Xanthogranulomatous endometritis is a rare benign pathology mimicking endometrial carcinoma.